Eksistensi Ruwatan Rambut Gimbal di Desa Dieng Kulon, Kecamatan Batur, Kabupaten Banjarnegara - In'am Zaidi; Nurjaya Nurjaya; Muhamad M. Muzadi (Universitas Negeri Medan, 2020)
The purpose of this study is to examine how the existence and role of the community in maintaining the dreadlocks of dreads in Dieng Kulon Banjarnegara, especially in the current era. The background of this research is characterized by the existence of Ruwatan dreadlocks children who are believed to be incarnations of Kyai Kolodete. This type of research is a qualitative research with a descriptive qualitative approach. Primary data were obtained through interviews with Dieng Indigenous Peoples and the community who carried out dreadlocks. The results showed that the existence of ruwatan dreadlocks in Dieng Kulon is still maintained until now. Evidence of this ruwatan still exists can be seen from the existence of the Dieng Culture Festival event. The keeksisan is influenced by some uniqueness in the implementation of the ruwatan, for example the determination of the time and place of implementation that must be adjusted to the wishes of the child dreadlocks. Then, related to the community's role in maintaining the strength of dreadlocks, the Dieng community continued to uphold the beliefs in the area. One of them is by continuing to carry out the dreadlocks of dreads whether done privately in their respective homes, or through the Dieng Culture Festival.